Glutamic Acid-Assisted Phytomanagement of Chromium Contaminated Soil by Sunflower (Helianthus annuus L.): Morphophysiological and Biochemical Alterations - Farid, Mujahid; Farid, Sheharyaar; Zubair, Muhammad; Ghani, Muhammad Awais; Rizwan, Muhammad; Ishaq, Hafiz Khuzama; Alkahtani, Saad; Abdel-Daim, Mohamed M.; Ali, Shafaqat (Frontiers in Plant Science, 2020)
Chelator-assisted phytoremediation is an economical, sustainable, and ecologically friendly method of extracting heavy metals and metalloids from the soil. Organic chelators are thought to enhance metal availability and mobility in contaminated media, thereby improving phytoextraction. The aim of the present study was to examine whether exogenous application of glutamic acid (GA) could improve chromium (Cr) phytoextraction by sunflower plants (Helianthus annuus L.). Seeds were planted in plastic pots filled with 5 kg of local agricultural soil spiked with increasing concentrations of Cr (1, 2, and 5 mg kg−1). Glutamic acid (5 mM) was applied to soil in solution according to a completely randomized experimental design and the sunflower plants were harvested after 8 weeks. The results indicated that increasing Cr-induced stress signiﬁcantly inhibited plant growth, leading to reduced biomass, photosynthetic pigment content, activities of antioxidant enzymes, and leaf area of the sunflower plants. However, exogenous addition of GA significantly reduced the Cr-associated toxic effects, while also increasing the accumulation of Cr in the plants. Moreover, increasing concentrations of Cr in the soil increased the generation of reactive oxygen species (ROS) responsible for the altered antioxidant enzyme activities. The results revealed that GA application to the topsoil enhanced the Cr concentration and accumulation in root, stem and leaves by up to 254%, 225%, 355% and 47%, 59%, 150% respectively. Further the GA addition reduced the Cr-induced toxicity in plants, and might be helpful for enhancing Cr phytoextraction by sunflower plants